2020
DOI: 10.2196/19985
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Seeking by Parents for Their Children: Systematic Review and Agenda for Further Research

Abstract: Background Parents commonly use the internet to search for information about their child’s health-related symptoms and guide parental health-related decisions. Despite the impact of parental online health seeking on offline health behaviors, this area of research remains understudied. Previous literature has not adequately distinguished searched behaviors when searching for oneself or one`s child. Objective The purpose of this review is to examine preva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 69 publications
12
110
3
Order By: Relevance
“…The features of this study’s results are comprehensive and not limited to specific countries and specific topics or issue-based research. Other HISB-related review studies reported specific data such as age, college enrollment, adulthood, needs, and disease, including adolescent disease [ 82 - 84 ]. However, in this study, the results of the analysis were based on a tool for surveying healthy adults, who account for the highest proportion of the population density.…”
Section: Discussionmentioning
confidence: 99%
“…The features of this study’s results are comprehensive and not limited to specific countries and specific topics or issue-based research. Other HISB-related review studies reported specific data such as age, college enrollment, adulthood, needs, and disease, including adolescent disease [ 82 - 84 ]. However, in this study, the results of the analysis were based on a tool for surveying healthy adults, who account for the highest proportion of the population density.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based health education and promotion has become increasingly popular among all age groups [1]. Although existing research on web-based health educational materials has focused on adults or general readers, there is an increasing body of research on the assessment and evaluation of web-based educational resources on children's health [2,3]. Clinical and academic research shows that effective writing styles can have an impact on the understanding and reception of medical and health educational resources for different reader groups [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the volume of information behavior research, conducting an overall literature review on this topic is challenging, and “reviews of the information behavior literature grew more specialized” (Case, 2006, p. 294). Literature reviews tend to focus on the information behavior of one group, such as youth (Agosto, 2019; Shenton, 2018), farmers (Phiri, Chipeta, & Chawinga, 2019), professors (Nwone & Mutula, 2019), consumers (Pian, Song, & Zhang, 2020; Zhao & Zhang, 2017), students (Mutula & Majinge, 2016; Oliveira & Greenidge, 2020; Spezi, 2016), parents (Kubb & Foran, 2020), medical or public health workers (Barr‐Walker, 2017; González‐Teruel, Campos‐Peláez, & Fortea‐Cabo, 2020; Prakasan, 2013), or people with impairments (Berget & MacFarlane, 2020). Other reviews tended to concentrate on studying one type of information, like health information (Chi, Pian, & Zhang, 2020; Kubb & Foran, 2020; Zhao & Zhang, 2017), musical information (Lavranos et al, 2016), or visual information (Albertson, 2015).…”
Section: Resultsmentioning
confidence: 99%